Enhanced Synthesis and Delivery of Magnesium Oxide Nanoparticles for Reverse Insulin Resistance in Type 2 Diabetes Mellitus - Jeevanandam, Jaison (Curtin University, 2017)
Type 2 diabetes has emerged to be a major threat to human health. The current study focuses on the formulation of a potential drug to reverse insulin resistance in adipose cells in order to enhance glucose uptake. As magnesium deficiency has proven to increase insulin resistance in diabetic patients, a formulation of magnesium oxide nanoparticles is proposed and proved as a potential drug for reversing insulin resistance and in treating type 2 diabetes.